2005
DOI: 10.1590/s0036-46652005000300010
|View full text |Cite
|
Sign up to set email alerts
|

Multiple brain abscesses due to Penicillium spp infection

Abstract: SUMMARYWe present a case of central nervous system (CNS) infection by a member of the Penicillium genera in a HIV-negative man in Brazil. The patient was admitted complaining of loss of visual fields and speech disturbances. CT scan revealed multiple brain abscesses. Stereothacic biopsies revealed fungal infection and amphotericin B treatment begun with initial improvement. The patient died few days later as a consequence of massive gastrointestinal bleeding due to ruptured esophageal varices. The necropsy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…Penicillium species are a species of fungi found as a part of normal flora of indoor and outdoor air, and approximately 225 subspecies have been defined to date. 9 The most potent pathogen of this group is Penicillium marneffei, which has a similar invasion capacity as Aspergillus species. 9 Systemic dissemination almost always occurs in patients with immunosuppression due to various reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penicillium species are a species of fungi found as a part of normal flora of indoor and outdoor air, and approximately 225 subspecies have been defined to date. 9 The most potent pathogen of this group is Penicillium marneffei, which has a similar invasion capacity as Aspergillus species. 9 Systemic dissemination almost always occurs in patients with immunosuppression due to various reasons.…”
Section: Discussionmentioning
confidence: 99%
“…9 The most potent pathogen of this group is Penicillium marneffei, which has a similar invasion capacity as Aspergillus species. 9 Systemic dissemination almost always occurs in patients with immunosuppression due to various reasons. 9 Clinical signs and symptoms suggestive of a posttransplant opportunistic CNSI should be taken seriously and investigated at once.…”
Section: Discussionmentioning
confidence: 99%
“…During the isolates' perform, the genus Penicilium was the most isolated fungi, meanwhile, a moderate frequency in the morning (8.86%) and in the afternoon (6.32%) periods was observed. Even so its presence becomes relevant by being involved in reported cases of disseminated infections (Ye et al, 2015), multiple brain abscesses (Noritomi et al, 2005), peritonitis (Böhlke et al, 2007) and pneumonia in immunocompromised patients (Oshikata et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mucocutaneous, oral, and facial manifestations that have been reported in patients with P. marneffei infection 25 were absent in this patient. Most such lesions are molluscum contagiosum-like umbilicated papules mainly distributed over the face and upper trunk 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive review of the English literature revealed only four cases of reported intracranial infection with Penicillium marneffei, with two of them in non-immunocompromised patients 26,28,29,30 .…”
Section: Discussionmentioning
confidence: 99%